1948
DOI: 10.1021/ie50461a032
|View full text |Cite
|
Sign up to set email alerts
|

Cumene Hydroperoxide in Redox Emulsion Polymerization

Abstract: retardation-namely, by the use of mixtures of normal and tertiary mercaptans and by an increase in the sodium hydroxide content of the system.The role of mercaptan in a recipe, such as given in Table I, is a dual one.It acts both as a chain initiator and as a chain transfer agent. The data in Table VI suggest that a DDM content of from 0.075 to 0.2 part should be sufficient to function as an initiator and that a tertiary mercaptan could then be used as modifier. This was verified in pilot plant experiments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1949
1949
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Table 4-1 shows a typical recipe for an emulsion polymerization [Vandenberg and Hulse, 1948]. This formulation, one of the early ones employed for the production of styrene-1,3-butadiene rubber (trade name: GR-S), is typical of all emulsion polymerization systems.…”
Section: -1b-1 Components and Their Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4-1 shows a typical recipe for an emulsion polymerization [Vandenberg and Hulse, 1948]. This formulation, one of the early ones employed for the production of styrene-1,3-butadiene rubber (trade name: GR-S), is typical of all emulsion polymerization systems.…”
Section: -1b-1 Components and Their Locationsmentioning
confidence: 99%
“…The main components are the monomer(s), dispersing medium, emulsifier, and water-soluble initiator. The dispersing medium is the liquid, usually water, Vandenberg and Hulse [1948].…”
Section: -1b-1 Components and Their Locationsmentioning
confidence: 99%
“…From experiments carried out in the absence of iron ( Fig. 15) it may be concluded that a large proportion of the CHP is consumed by di- (1) no Fe(N0&.9HzO; (2) 0.0022 part of Fe(N03)8*9Hz0; (3) 0.009 part of Fe(N03)3. ~H z O ; (4) 0.036 part of Fe(N03)3*9HzO; (5) 0.144 part of Fe(NO3)s9HzO.…”
Section: Use Of Various Complexing Agentsmentioning
confidence: 98%
“…~H z O ; (4) 0.036 part of Fe(N03)3*9HzO; (5) 0.144 part of Fe(NO3)s9HzO. (1) no irop, no salt; (2) 0.036 part of Fe(N03)3.9Hz0, 0.5 part of KzSO4; (3) 0.036 part of Fe(N03)3.9H20, 0.5 part of Na4PzOr10Hz0; (4) no iron, 1 part of Na4P&-1OHzO.…”
Section: Use Of Various Complexing Agentsmentioning
confidence: 99%
See 1 more Smart Citation